HEALTHY IN THEORY, INDULGENT IN PRACTICE: EXPLAINING THE GEN Z BEVERAGE CONSUMPTION PARADOX IN AN EMERGING MARKET - Tolipov Saidkhuja Nuriddin o’g’li (Modern American Journals, 2026)
Generation Z is frequently portrayed as the most health-conscious consumer cohort, characterised by heightened awareness of nutrition and long-term wellbeing (Francis & Hoefel, 2018; Dwidienawati et al., 2020). Paradoxically, however, high-sugar beverages remain present in their consumption patterns. This study examines this contradiction using survey data from 120 Generation Z consumers in Uzbekistan, an under-researched emerging market context. Although respondents reported strong concern about sugar intake and recognised associated health risks, these attitudes showed limited influence on actual consumption behaviour, particularly in social settings. Correlation and regression analyses revealed that health consciousness was not a significant predictor of reduced sugary beverage consumption, whereas social consumption contexts were positively associated with higher intake. These findings challenge the assumption that Gen Z’s health awareness consistently translates into behavioural change. The study introduces the concept of contextualised health dissonance, suggesting that health values coexist with socially legitimised indulgence. This contributes to consumer behaviour theory by highlighting the situational and cultural limits of health-driven consumption among young consumers.
Keywords: sugary beverage consumption